PEMBERDAYAAN USAHA MIKRO BINAAN LAZISMU BANYUMAS MELALUI PEMAHAMAN AKAD PEMBIAYAAN SYARIAH - encep saepudin (ITB AAS INDONESIA Surakarta, 2023)
Micro-enterprises contribute greatly to the economy and regional development. However, the development of its business scale faces a number of problems, including not being managed with modern management, low quality of human resources (HR), and limited ability to manage finances and access to capital. This study aims to determine the level of understanding of micro-businesses assisted by Lazismu Banyumas towards Islamic financial institutions (LKS) and Islamic financing products. His understanding will have an impact on access, management, and his ability to increase the scale of his production so that he can become an independent and muzakki business. This study uses a qualitative method with a case study approach in which 10 respondents were selected based on an agreement with Lazismu Banyumas. The result of the research is that micro-enterprises still need additional capital and assistance to develop their businesses. Their understanding of Islamic financial institutions is minimal so they cannot access Islamic bank products, but some others deliberately refuse Islamic bank financing because they are considered the same as Islamic banks and are afraid of not being able to return it.